The sound of silence: autosomal recessive congenital ichthyosis caused by a synonymous mutation in ABCA12. Issue 4 (26th March 2013) - Goldsmith, Tomer; Fuchs‐Telem, Dana; Israeli, Shirli; Sarig, Ofer; Padalon‐Brauch, Gilly; Bergman, Reuven; Indelman, Margarita; Sprecher, Eli; Nousbeck, Janna
Abstract: Autosomal recessive congenital ichthyosis refers to a heterogeneous group of cornification disorders of major impact on patients' life. The disease has been linked so far to mutations in 8 distinct genes. We report a consanguineous family of Arab Muslim origin with several members displaying a severe form of congenital ichthyosiform erythroderma. Using a panel of polymorphic microsatellite markers, we identified a region of homozygosity shared by all patients on 2q34, in a region harbouring the ABCA12 gene. Direct sequencing of genomic DNA derived from a patient failed to reveal any obviously pathogenic change in the coding sequence of this gene. In contrast, cDNA sequence analysis revealed the existence of a 163‐bp‐long deletion in exon 24, thus pointing to a splicing defect. Careful reanalysis of the genomic DNA sequence revealed apart from several known single‐nucleotide polymorphisms, a hitherto unreported homozygous synonymous mutation in exon 24 (c.3456G>A; p.S1152S), which was found to lead to the formation of a novel splicing acceptor site. Synonymous mutations have been shown to uncommonly cause inherited disorders in humans. Here, we present the first example of a congenital form of ichthyosis resulting from such a genetic defect.